Malignant Bowel Obstruction in Patients With Recurrent Ovarian Cancer. (April 2016) - Tran, Elizabeth; Spiceland, Clayton; Sandhu, Nicole P.; Jatoi, Aminah
We sought to report incidence, risk factors, and survival related to bowel obstruction in 311 ovarian cancer patients with recurrent disease. A total of 68 (22%) had a documented bowel obstruction during their cancer course, and 49 (16%) developed it after cancer recurrence. Surprisingly, 142 (45%) fit into an "unknown" category (3+ months of data lacking from last contact/death). No risk factors were identified; management included surgery (n = 21), conservative measures (n = 21), and other (n = 7). Documented bowel obstruction was not associated with a statistically significant reduction in survival after cancer recurrence. In conclusion, although bowel obstruction occurs in only a subgroup of patients with ovarian cancer and does not appear to detract from survival after cancer recurrence, limited end-of-life information may be resulting in an underestimation of incidence.